"This is civil disobedience. I'll continue.": the racialization of school board meeting rules. Issue 2 (4th March 2022) - Sampson, Carrie; Bertrand, Melanie
ABSTRACT: Minoritized communities throughout the world engage in spaces of educational decision-making to advocate for equity-oriented policies. In this article, we explore such advocacy at the local level in school board meetings in the United States. Specifically, we examine school board meeting rules from meetings featuring the advocacy of mainly Black community members who aimed to address inequities in a suburban school district governed by a largely white school board. Informed by the theories of community cultural wealth and whiteness as property, we used qualitative case study methods to analyze board meeting videos to understand how rules facilitate opportunities for advancing or inhibiting equity-oriented policymaking at the district level. Illustrating the racialization of school board meeting rules, our findings emphasize how community advocates enacted resistance and navigational strategies to work around rules that board members used to maintain and reify whiteness as property. We conclude with implications for enhancing opportunities for equity-oriented policymaking via school board meetings and other local educational spaces of decision-making and for future research.